Mengidentifikasi Minat Belajar Bahasa Arab pada Siswa - Aswan, Ahmad Rathomi (Fakutas Tarbiyah Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2022)
Interest is one of the psychological aspects that can encourage someone to achieve a goal. Someone who has an interest in an object tends to pay attention and have a greater sense of pleasure to that object. Therefore, interest is a very important aspect in the context of learning, especially Arabic learning. The achievement of learning objectives is strongly influenced by students' interest in Arabic. This research uses a qualitative approach with the type of library research. Data was collected and analyzed using content analysis techniques. Based on the analysis, to identify students' interest in Arabic learning can be seen in the aspects of attention, interest, willingness and pleasure.